CCL3 and CCL4 are biomarkers for B cell receptor pathway activation and prognostic serum markers in diffuse large B cell lymphoma. (11th September 2015) - Takahashi, Koichi; Sivina, Mariela; Hoellenriegel, Julia; Oki, Yasuhiro; Hagemeister, Fredrick B.; Fayad, Luis; Romaguera, Jorge E.; Fowler, Nathan; Fanale, Michelle A.; Kwak, Larry W.; Samaniego, Felipe; Neelapu, Sattva; et al.
Summary: B cell receptor (BCR) signalling is an important pathway in diffuse large B cell lymphoma (DLBCL). In response to BCR triggering, normal and malignant B cells secrete the chemokines CCL3 and CCL4 to attract accessory cells to the tissue microenvironment. We measured CCL3 and CCL4 serum concentrations in 102 patients with newly diagnosed DLBCL by enzyme‐linked immunosorbent assay, investigated their prognostic impact and validated our findings in an independent cohort of 51 patient samples. We also tested CCL3 and CCL4 secretion by DLBCL cells, and the influence of BTK inhibitors on the secretion of these chemokines. High CCL3 (≥40 pg/ml) serum concentrations correlated with higher international prognostic index, lactate dehydrogenase and β2 microglobulin, as did CCL4 (≥180 pg/ml) with advanced Ann Arbor stages. High CCL3 levels correlated with significantly shorter progression‐free and overall survival. The in vitro studies demonstrated that activated B cell‐like, but not germinal centre B cell‐like DLBCL cells, secrete high levels of CCL3 and CCL4 after BCR triggering, which was exquisitely sensitive to BCR pathway inhibition. These findings support CCL3 and CCL4 protein concentrations as biomarkers for BCR pathway activation and prognosis in DLBCL.